Responses of germination, photosynthesis, and gene expression in four cotton varieties under drought stress - Baha, Jiazila; Zhao, Xiaohong; Li, Yage; Zhai, Xue; Cao, Xinchuan; Guo, Weifeng (Frontiers in Plant Science, 2026)
BackgroundDrought is a crucial abiotic stress factor affecting the growth and development of cotton, and there is significant differentiation in drought resistant among different cotton varieties. To reveal the drought resistance mechanisms of four cotton varieties, this study conducted a systematic analysis across multiple stages and multiple indicators. MethodsIn this study, two drought resistant varieties (J206-5 and Jiumian 20) and two drought sensitive varieties (Xinluzhong 77 and Xinluzhong 67) were selected as experimental materials for seed germination, drought related gene expression during seedling stage, and photosynthetic indicators during flower and boll stage. ResultsThe six germination indicators of four cotton varieties showed a decreasing trend with the increase of PEG6000 concentration. Under 10% PEG6000 treatment, the relative germination potential, relative germination rate, relative germination index, and relative root fresh weight of drought resistant varieties were significantly higher than those of drought sensitive varieties. Under drought stress until July 19th, the Pn, Tr, and SPAD of drought resistant varieties were significantly higher than those of drought sensitive varieties. Under drought stress until August 19th, the Ci and SPAD of drought resistant varieties were significantly higher than those of drought sensitive varieties, and the Pn of drought resistant varieties was significantly higher than that of drought sensitive variety Xinluzhong 67. When drought resistant varieties were subjected to drought stress for 8d, except for the GhPPO-3 gene, the expression levels of the other 8 genes were significantly upregulated and reached their maximum values, and the expression levels were significantly higher than those of drought sensitive varieties. ConclusionUnder drought stress, drought resistant cotton varieties exhibit better seed germination, photosynthesis, and expression levels of drought related genes. This study provides a theoretical basis for cotton drought resistance breeding.